Analysis of Volatile Polycyclic Aromatic Hydrocarbons in Environmental Water Using Headspace Microextraction Based on a Polyurethane Sponge-Supported Liquid Film Combined with Gas Chromatography-Mass Spectrometry - Xu XU; Shi-ping ZHAO; Zhu-chen HOU; Yan-xin WANG; Yu-meng LIU; Jia LYU; Bao-cheng JI; Yan-hong BAI (Zhipu Xuebao, 2024)
A method of combining headspace microextraction technique based on a polyurethane sponge-supported liquid film with gas chromatography-mass spectrometry (GC-MS) was developed for convenient and sensitive analysis of six polycyclic aromatic hydrocarbons (PAHs) in environmental water samples. The microextraction device consists of three parts, namely injector, polyurethane sponge, and headspace bottle. Firstly, the commercially available polyurethane sponge was specially tailored to be fitted into miniature cylinders that were compatible with the internal cavity of the 2.5 mL syringe needle. Then the extraction solvents were loaded to form a microextraction liquid film on the surface and inside of the sponge. After sealed with syringe barrel, the syringe needle was inserted into the septum of headspace bottle for headspace microextraction. The dynamic suction, heating assistance, and magnetic stirring were adopted to accelerate the volatilization process and transferring of the analytes in gas-liquid interface. Given the excellent elasticity of polyurethane sponge, the extraction solution could be successfully recovered through solvent elution and physical extrusion. The influence of the types and amounts of extraction solvents, suction time, heating (extraction) temperatures, stirring speeds, and eluent volumes on the enrichment efficiency of the monitored PAHs were systematically investigated. The results indicated that the satisfactory extraction efficiency could be achieved by using 40 µL of carbon tetrachloride as an extractant, which were loaded into a polyurethane sponge microcylinder with a bottom diameter and height of 4 mm, and followed by 150 cycles dynamic suction under extraction conditions of 65 ℃ and 1 000 r/min. Subsequently, physical extrusion was adopted to collect the extraction solution after elution with 30 µL of carbon tetrachloride. The validation results demonstrated that the proposed method achieves good relative recoveries of PAHs ranging from 94.7% to 113.2% at three spiked levels of 0.1, 0.5, and 1 μg/L. The intra- and inter-day precisions are in the range of 1.0%-8.1% and 4.2%-9.5%, respectively. Good linearities are observed for all monitored PAHs with the regression coefficients (R2) greater than 0.997 in the concentration range of 0.01-5 μg/L. The limits of detection (LODs) and quantification (LOQs) are in the range of 3-30 ng/L and 10-100 ng/L, respectively. This method is easy to operate, and has the advantages of low cost, high sensitivity as well as fast speed, having highly potential in the field of trace volatile analysis in environmental samples.